The Effectiveness of Instagram on The Sales Performance of Msmes in South Kalimantan Within the Context of Post Digital Fatigue - Rindiani Amelia; Ignatius Ismojo Herdono (Publikasi Indonesia, 2025)
Digital transformation is often promoted as a solution to improve the marketing performance of MSMEs. However, in the context of ultra-micro businesses in South Kalimantan, the impact does not always align with this narrative. This study examines the influence of post-digital fatigue , perceived effectiveness of Instagram, and the length of time the business has been active on the platform on MSMEs' perceptions of increased sales. A quantitative approach was used with 204 ultra-micro business owners in 13 districts/cities, analyzed using ordinal logistic regression. The results show that all three variables significantly influence perceptions of increased sales. These findings indicate that digital stress can become a psychological and operational burden rather than guaranteeing sales success. This study contributes to the literature on micro-sector digitalization and emphasizes the need for more contextual and applicable digital training.